2017
DOI: 10.1007/s00167-017-4532-8
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of all complex Segond avulsion using ultrasound imaging

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 23 publications
2
35
0
1
Order By: Relevance
“…Radiographs are considered the gold standard when investigating Segond fractures, 8 but as discussed formerly, the use of other radiological modalities might help establish the relationship between this bony avulsion and the high incidences of ALC soft tissue injuries. 19,22 Given that very few studies have related clinical evaluation of anterolateral rotational instability to imaging signs of anterolateral injury, the clinical correlate of the Segond fracture still has to be settled. Another limitation of the current work is the slight change in surgical techniques throughout the study period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiographs are considered the gold standard when investigating Segond fractures, 8 but as discussed formerly, the use of other radiological modalities might help establish the relationship between this bony avulsion and the high incidences of ALC soft tissue injuries. 19,22 Given that very few studies have related clinical evaluation of anterolateral rotational instability to imaging signs of anterolateral injury, the clinical correlate of the Segond fracture still has to be settled. Another limitation of the current work is the slight change in surgical techniques throughout the study period.…”
Section: Discussionmentioning
confidence: 99%
“…6,13 Other authors have studied the bony avulsion with ultrasound and suggested that dynamic ultrasound might be used to better visualize associated ligament injury. 19 With the recent debate on anatomic features and biomechanical properties of the anterolateral complex, including the anterolateral ligament, new light has been shed on the potential importance of injuries to the anterolateral aspect of the knee. 12,13,18 Some authors have questioned if the Segond fracture represents a bony avulsion of the tibial anterolateral ligament insertion.…”
mentioning
confidence: 99%
“…The authors used only plain radiographs and MRI to evaluate for the presence of SF. However, it is recognised that these imaging modalities are not as sensitive as ultrasound, which detects SF at a rate of approximately 30% in ACL injured knees 8. From proximal to distal, several portions of the ALL can be injured 18.…”
Section: Discussionmentioning
confidence: 99%
“…Klos et al reported a much higher rate of detection (30%) when using US. 11 Cavaignac et al found a large difference in the detection rate of Segond lesions based on plain radiographs (3.3%), MRI (13%) and US (50%). 1 Ultrasonography makes it possible to detect a certain number of Segond fractures that are not fractures by definition, but actually unicortical lesions over the ALL's tibial insertion.…”
mentioning
confidence: 96%